Maternal protein restriction impairs nutrition and ovarian histomorphometry without changing p38MAPK and PI3K-AKT-mTOR signaling in adult rat ovaries - Côrtes, Lucas Silva [UNESP]; Silveira, Henrique Spaulonci [UNESP]; Lupi, Luiz Antonio [UNESP]; de Mello Santos, Talita [UNESP]; Cavariani, Marilia Martins [UNESP]; Domeniconi, Raquel Fantin [UNESP]; Gaiotte, Letícia Barbosa [UNESP]; de Morais Oliveira, Diego Augusto [UNESP]; Justulin, Luis Antonio [UNESP]; Chuffa, Luiz Gustavo de Almeida [UNESP] (Elsevier, 2021)
Aims: Because an adequate protein supply is detrimental for the maintenance of folliculogenesis and ovulation, we evaluated the impact of maternal low protein diet on nutritional parameters, estrous cycle, ovarian histomorphometry, and on the expression of metabolic and survival signaling molecules in different follicular stages. Main methods: Twenty Wistar pregnant rats were divided into two groups: the normoprotein (NP) group, composed of animals that received 17% protein, and a low-protein (LP) group, composed of animals that received 6% protein during gestation and lactation period. After weaning, female rats were fed with standard diet until the 120-days-old. Key findings: LP animals showed reduced body mass index, total body weight, energy intake, feed efficiency, and visceral fat. The ovarian tissue presented vascular congestion and fat accumulation in the medulla, followed by a significant reduction in the amount of primordial and primary follicles. In addition, the number of atretic follicles was higher in LP than in NP animals. Maternal undernutrition also resulted in increased levels of estradiol (E2) and progesterone (P4) while testosterone (T) was unchanged in the offspring. Although discrete changes in p38MAPK and in PI3K-AKT-mTOR immunostaining were observed in the ovarian follicles and corpus luteum in LP, no differences were found at their protein levels. Significance: Maternal protein restriction alters estrous cycle and histomorphometry of the offspring's ovary without changing the levels of intracellular regulatory molecules in adulthood. These morphofunctional changes may alter reproductive performance in female offspring, highlighting maternal dietary conditions as an important factor for offspring reproductive health.
Keywords: AKT; DOHaD; Estrous cycle; Low-protein diet; MAPK; Maternal restriction; mTOR; Ovarian tissue; PI3K